Vitamin D deficiency among the patients attending B. P. Koirala Institute of Health Sciences: a cross sectional study - Chaudhari, Rajendra K.; Shah, Cosmica; Raman, Ananya; Yadav, Dikshya; Gelal, Basanta (International Journal of Scientific Reports, 2021)
Background: Vitamin D deficiency has become a public health problem worldwide regardless to geography. Vitamin D deficiency leads to osteoporosis and also associated with metabolic syndrome, cardiovascular diseases, obesity, diabetes and autoimmune disorders. Early detection of vitamin D level in blood followed by supplementation can prevent various chronic diseases. There are limited studies of vitamin D deficiency from eastern Nepal therefore we planned to assess the prevalence of vitamin D in different age groups and gender among patients visiting at BPKIHS. Methods: This descriptive cross-sectional study was done among the patients attending Immunoassay laboratory of the BPKIHS. Based on purposive sampling technique, data of first visit of patients were taken who came for investigation of vitamin D from January to March, 2019. Serum 25 (OH) vitamin D levels were measured by CLIA method using Maglumi 2000 (Snibe Co. Ltd, Shenzhen, China). Results: A total of 2399 (73.81%) female and 851 (26.19%) males were enrolled in the study among which 66 (2.03%), 133 (4.09%) and 3051 (93.88%) were children, adolescent and adult respectively. This study revealed 61.2%, 27.6% and 11.2% patients having deficient, insufficient and sufficient level of serum vitamin D respectively. Significantly, highest percentages of adolescents were found vitamin D deficient compared to adults and children. Adolescents have shown significantly low median levels of vitamin D (p<0.001). Conclusions: Prevalence of vitamin D deficiency is higher in patients visiting BPKIHS. Comparatively higher percentage of vitamin D deficiency and low vitamin D levels are reported among adolescents compared to children and adult.